Evaluasi Kepuasan Pengguna Terhadap System Application and Product Menggunakan Metode SUS dan PIECES Framework - Mulyono, Andronikus; Nataliani, Yessica (STIKOM Tunas Bangsa Pematangsiantar, 2024)
User satisfaction with a system is a response to assess the good and bad of a system used in an organization or company. In addition, user satisfaction is also used as a reference for system developers to improve the performance of information systems that have been built. PT XYZ as a company engaged in tea management uses System Application and Product (SAP) oriented Enterprise Resources Planning (ERP) in the form of software to carry out various work activities in the company's business processes. However, there are still various problems of dissatisfaction with the use of SAP software. Because one of the objectives of using the software is to support operations at the company, it is necessary to evaluate with the aim of measuring user satisfaction with SAP. In this research, two methods are used, namely the System Usability Scale (SUS) and the PIECES framework. Based on the research results, the SUS method has a value of 62.79 with the